CHANGING THE CHARACTERIISTICS OF THE ENGINE OIL DURING OPERATION OF THE CUMMINS ENGINE BUS FLEET OF THE CITY OF OMSK - S. V. Korneev; S. V. Pashkevich; A. S. Savos’kin; I. I. Shirlin (Вестник СибАДИ, 2017)
This article presents the results of expert assessment of the technical condition of the diesel engine 6ISB Cummins 245 B that is installed on the buses of LiAZ 525653. The specified bus participated in field tests of a motor oil of G-Profi MSI Plus SAE 15W-40 API CI-4/SL, manufactured “Gazpromneft – SM”. To determine the effect of the above engine oil on the technical condition of the engine under the control of the bus was conducted a complex of works on assessment of technical condition of the engine. Examines the changing characteristics of engine oils as kinematic viscosity, base number, and also evaluated the tribological properties of the content of wear products. The conclusions about the feasibility of using the investigated engine oil during operation of the bus fleet of Omsk.